-7x+6x+4=-6x+6x-3

Simple and best practice solution for -7x+6x+4=-6x+6x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+6x+4=-6x+6x-3 equation:



-7x+6x+4=-6x+6x-3
We move all terms to the left:
-7x+6x+4-(-6x+6x-3)=0
We add all the numbers together, and all the variables
-7x+6x+4-(-3)=0
We add all the numbers together, and all the variables
-1x+7=0
We move all terms containing x to the left, all other terms to the right
-x=-7
x=-7/-1
x=+7

See similar equations:

| 10c–6=10c+7 | | (t-3)/2=75 | | -2-4/5x=13 | | 28=1/2•7h | | 10(x-1)=4 | | 700–35w=450+15w | | X+9÷2=3x | | x^2=6(x-3) | | 2(x-6)=32 | | 2(x+6)=-2(x+4) | | n/4-21=-3 | | a=5+-5a+5 | | y/15.36+5=11 | | -12=n/2=6 | | 4/5w=164/5 | | 130+45x=70+45x | | 4/5=24/(x+5) | | 90x-60=120 | | 4x^2-59x+207=0 | | 3(c-6)=78/3 | | -1.75=p+4.85 | | x-34=-40 | | 2w(w+1)(w-5)=0 | | 3-1/2x=-4.5 | | 10+3(x-1)=39 | | 7y-6=-10+8(3y-8) | | -4x+-8=4x | | -15.9=u/8-3.1 | | 3/4x-8+5/8=3 | | 2x÷2=8 | | .75(e)=2-1.25e | | 2(2+4)2+4x=x(3+3)+2 |

Equations solver categories